Student engagement: A multidimensional measurement scale applied to blended course modalities at the university level - Heilporn, Géraldine; Lakhal, Sawsen; Bélisle, Marilou; St-Onge, Christina (Mesure et évaluation en éducation)

(untitled) (ADMEE-Canada - Université Laval, 2020)
Blended course modalities combine synchronous activities (face-to-face or in virtual classrooms) with asynchronous online activities, and they represent a fertile ground for enhancing student engagement. However, studying student engagement in these environments requires the development of a measurement scale, which is the purpose of this paper. This new measurement scale for student engagement in blended course modalities (EMEECH) provides researchers and instructors with tools for assessing student engagement in blended course modalities (blended, blended online, or blended synchronous) from a multidimensional perspective. This article presents the scale development, along with validity evidence for its internal structure obtained through exploratory factor and internal consistency analyses, based on diversified data from three universities. A first sample (n1=234) allowed for identifying three dimensions of student engagement: emotional-cognitive, social, and behavioral. A second sample (n2=231) provided further evidence of the internal structure of the new scale by confirming its factorial structure and its superior internal consistency.